IMPLEMENTATION OF DOUGH MOULDING MACHINE AS A LEARNING MEDIA TO IMPROVE MACHINE ELEMENTS LEARNING OUTCOMES - Janualdi, Yakub; Hudan (Jurusan Pendidikan Teknologi Dan Kejuruan, 2023)
Using a dough moulding machine as a learning tool, improving student learning outcomes in the Machine Elements course, and planning the transmission of belts and pulleys for dough moulding machines were the three goals of this study. Classroom Action Research (CAR) was the method employed in this study. According to the results, the dough moulding machine was implemented as a teaching tool in the Machine Elements course over the course of two cycles, with each cycle consisting of the planning, action, observing, and reflecting phases. In the study's conclusion, it is stated that the use of teaching aids in the Machine Elements course can enhance student learning outcomes. An increase from cycle I to cycle II was indicative of improved learning outcomes. The percentage of student learning outcomes that are completed has increased, with the first cycle's completion rate reaching 56,25% of students and the second cycle's completion rate reaching 100 percent of the 16 students who achieve KKM > 60. Each cycle is characterised by an increase in the assessment of student attitudes and skills.